2018
DOI: 10.1038/nature25986
|View full text |Cite
|
Sign up to set email alerts
|

Itaconate is an anti-inflammatory metabolite that activates Nrf2 via alkylation of KEAP1

Abstract: The endogenous metabolite itaconate has recently emerged as a regulator of macrophage function, but its precise mechanism of action remains poorly understood. Here we show that itaconate is required for the activation of the anti-inflammatory transcription factor Nrf2 (also known as NFE2L2) by lipopolysaccharide in mouse and human macrophages. We find that itaconate directly modifies proteins via alkylation of cysteine residues. Itaconate alkylates cysteine residues 151, 257, 288, 273 and 297 on the protein KE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
1,449
10
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,319 publications
(1,632 citation statements)
references
References 30 publications
69
1,449
10
6
Order By: Relevance
“…Chemicals, reagents and antibodies OI was synthesized by Min-de Biotech (Suzhou, China) based on a previously described protocol [16]. Lipopolysaccharide (LPS) and puromycin were purchased from Sigma-Aldrich Co. (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chemicals, reagents and antibodies OI was synthesized by Min-de Biotech (Suzhou, China) based on a previously described protocol [16]. Lipopolysaccharide (LPS) and puromycin were purchased from Sigma-Aldrich Co. (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…We first tested the potential effect of OI, the cell-permeable derivative of itaconate [16], on Nrf2 signaling in THP-1 human macrophages [31,32]. By performing the coimmunoprecipitation assay, we showed that treatment with OI (25 μM, 2 h) disrupted the association between Keap1-Nrf2 in THP-1 cells (Fig.…”
Section: Oi Activated Nrf2 Signaling In Thp-1 Cells and Sle Patient-dmentioning
confidence: 99%
See 3 more Smart Citations